2017
DOI: 10.1002/ijgo.12088
|View full text |Cite
|
Sign up to set email alerts
|

Birth characteristics of Syrian refugees and Turkish citizens in Turkey in 2015

Abstract: Cesarean delivery is more common among pregnant Turkish citizens than among Syrian refugees. Other notable differences between the groups were recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
37
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 16 publications
9
37
2
4
Order By: Relevance
“…But in our study, this rate was found to be as low as 15%, and there was no statistical difference between the groups. Similarly, two previous studies done in Turkey demonstrated lower Csection rates among nulliparous Syrian patients; 13,14 they reported that their control groups were more likely to show the complications of GDM and preeclampsia. Our hospital is a reference hospital for high-risk pregnancies and older maternal age.…”
Section: Discussionmentioning
confidence: 53%
“…But in our study, this rate was found to be as low as 15%, and there was no statistical difference between the groups. Similarly, two previous studies done in Turkey demonstrated lower Csection rates among nulliparous Syrian patients; 13,14 they reported that their control groups were more likely to show the complications of GDM and preeclampsia. Our hospital is a reference hospital for high-risk pregnancies and older maternal age.…”
Section: Discussionmentioning
confidence: 53%
“…The finding from this study assists nurses in Turkey to be more conscious of individual and social factors that are barriers for prenatal or postpartum refugee mothers. While many of these factors are related to being a refugee more broadly, the need for information in women’s own language is important, as it has been shown that the establishment of special care guides in their own language facilitates access to health services (Correa‐Velez & Ryan, ; Demirci et al, ). At the same time, it is necessary to have a sufficient number of interpreters in hospitals so that women do not feel alone during birth (Büyüktiryaki, Canpolat, Dizdar, Okur, & Şimşek, ).…”
Section: Discussionmentioning
confidence: 99%
“…The city of Bursa, in which our study was conducted, is the fifth largest city in Turkey based on population density. Bursa currently hosts over 340,000 Syrian refugees and provides the perfect backdrop for our study [10,12]. We found that 29% of our refugee population preferred condoms as a birth control method while 24% preferred to use oral contraceptive pills (OCP) (Figure 1).…”
Section: Discussionmentioning
confidence: 97%
“…Although the refugee population has a high birth rate, the data about the method of delivery is inconsistent. These inconsistencies arise based on the reported number of cesarean sections among the Syrian refugee population [2,3,9,10]. In one study conducted in Turkey it was shown that the cesarean section rate is higher in Turkish women than in the Syrian refugees [10].…”
Section: Discussionmentioning
confidence: 99%